Clinical, Biochemical, Molecular, and Outcome Features of Mitochondrial 3-Hydroxy-3-Methylglutaryl-CoA Synthase Deficiency in 10 Chinese Patients - Wu, Shengnan; Shen, Linghua; Chen, Qiong; Gong, Chunxiu; Yang, Yanling; Wei, Haiyan; Cao, Bingyan; Chen, Yongxing (Frontiers in Genetics, 2022)
Background: Mitochondrial 3-hydroxy-3-methylglutaryl-CoA synthase deficiency (HMGCS2D) is a rare autosomal recessive metabolic disorder caused by mutations of the HMGCS2 gene. To date, no more than 60 patients have been reported throughout the world. Purpose: To analyze the clinical, biochemical, molecular, and outcome features of HMGCS2D in a case series of 10 new Chinese patients. Methods: This retrospective study includes 10 Chinese patients diagnosed with HMGCS2D. We collected and analyzed their clinical data. We also reviewed clinical data for 39 cases that had been reported previously. Results: All of our patients had experienced their first metabolic crisis before 12 months old. The most common clinical manifestations were anorexia, dyspnea, and disturbance of consciousness (10/10), followed by vomiting (8/10), fever (7/10), cough (4/10), diarrhea, and seizures (3/10). Each patient (10/10) had a different degree of hepatomegaly and increased aminotransferase, severe metabolic acidosis, and hypofibrinogenemia. 9 patients presented with severe hypoglycemia and weak positives on qualitative tests of urinary ketone body. Patient 3 was the only one without hypoglycemia. Five patients had hypocalcemia, five patients had hyperammonemia, four patients had hyperuricemia, and three had hypertriglyceridemia. During the metabolic acidosis episode, we observed high dicarboxylic acid values in urine, and the elevated ratio of blood acetylcarnitine to free carnitine may have been an additional biochemical signature. However, all returned to normal during the interictal interval. Molecular analysis identified 15 variants in the HMGCS2 gene, of which 10 were novel (c.220G>A/p.E74K, c.407A>G/p.D136G, c.422T>A/p.V141D, c.719A>C/p.D240A, c.821G>A/p.R274H, c.39dupA/p.L14Tfs*59, c.1394delA/p.N465Tfs*10, c.788delT/ p.L263Cfs*36, c.717T>G/p.Y239*, and c.1017-2A>G). Combining these with previous cases, the known mutation c.1201G>T/p.E401* has been found in 6/40 (15.0%) of mutated alleles in 21 Chinese patients, while none have been found in other populations. We found that patients with biallelic truncation mutation appeared to show a more severe clinical condition through a literature review. Conclusion: This study analyzed the phenotypic and genetic features of HMGCS2D in a Chinese case series. We expanded the HMGCS2 mutational spectrum with 10 novel variants. The c.1201G>T/p.E401* mutation was the most frequent, representing 15.0% of the mutated alleles in reported unrelated Chinese patients, and thus, it may be a hot spot mutation.